Peningkatan Kesehatan dengan Senam Lansia di Posyandu Lansia - Nety Mawarda Hatmanti (Universitas Islam Nahdlatul Ulama Jepara, 2022)
Background: The implementation of health service activities in the community during the pandemic was disrupted due to the Covid-19 pandemic. Elderly is one of the groups who are vulnerable and at risk of disease. With the normal era, the activities of the Elderly Posyandu began to be reactivated and the elderly began to take part in routine activities for 1x a week for physical examinations and 1x a month for elderly exercise activities to improve health and body fitness. The purpose of this activity is to improve the health and fitness of the elderly by implementing elderly gymnastics and health checks. Methods: The activities carried out included health checks (blood pressure, random blood sugar levels, uric acid and cholesterol) and the implementation of elderly gymnastics at the Elderly Posyandu, Menanggal Village, Surabaya. Blood pressure checks using a digital sphygmomanometer and other checks using an easy touch brand. Implementation of gymnastics using video media on YouTube about elderly gymnastics. Results: The elderly who took part in the examination and exercise activities were very enthusiastic in participating in the activities. The results of the examination of 22 elderly people showed that 47.4% were in the category II hypertension, 63.6% uric acid > normal, 72.7% cholesterol above normal. Conclusion: In addition to participating in activities at the Elderly Posyandu, the elderly must continue to carry out activities at home actively and productively so that they are always fit and healthy.